Gharbi Noura - Gharbi, Noura (Université Mohamed BOUDIAF de M'Sila, 2014)
We attacked in this physical study of the master memory in physics of the particles high energy the application of the Schrödinger equation on the hydrogen atom under the action of a potential Colombian in the ordinary and non commutative space at two dimensions, and we compared between the results in the two spaces. We notice that the non commutative space gives the same results gotten in the ordinary space under the action of a magnetic field.
Keywords: Schrödinger equation, ordinary space, non commutative space